1990
DOI: 10.1177/027836499000900506
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Methodology for Motion Planning with Uncertainty for 2D and 3D Two-Link Robot Arm Manipulators

Abstract: Most of the work on robot path planning revolves around two basic models: the model with complete information (often called the "Piano Mover's Problem") and the model with incomplete information (called here the "South Pole Search Problem'). The approach of dynamic path planning introduced in Lumelsky and Stepanov (1987) and Lumelsky (1987) is based on the latter model and produces nonheuristic (provable) algorithms for simple robot arm manipulators operating in an environment with unknown obstacles of arbitra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…cl Now let us define a connectivity graph 9 for the torus similar to Definition 3.1, except that the one generic path used in the definition is replaced with the three of a complete set. That is, the connectivity graph is formed by the obstacle boundaries together with the portions of a complete set of generic paths outside of obstacles.…”
Section: Connectivity Graph In a Torusmentioning
confidence: 99%
See 1 more Smart Citation
“…cl Now let us define a connectivity graph 9 for the torus similar to Definition 3.1, except that the one generic path used in the definition is replaced with the three of a complete set. That is, the connectivity graph is formed by the obstacle boundaries together with the portions of a complete set of generic paths outside of obstacles.…”
Section: Connectivity Graph In a Torusmentioning
confidence: 99%
“…For fixed and 02, there exist two 'elbow positions' for e4: the up-elbow position corresponds to e4 > 0, and the down-elbow position to O4 < 0 two degrees of freedom, and its configuration space presents a torus. It is shown in [9] that the configuration space of all two-link planar or spatial robot arm manipulators with prismatic or revolute joints presents a compact subset of a torus with obstacles being simple closed curves on the surface of the torus, and in [20] that the configuration space of a certain class of three-link robot arm manipulators can be deformed into a 2D compact surface.…”
Section: Introductionmentioning
confidence: 99%
“…Path planning is used for a range of applications from optimal-path navigation [1], [2] to exploration [3], [4] to the movement of robotic arms in manufacturing plants [5], [6]. Many different constraints have been explored, including formations of robots, kinematic properties of vehicles, and robotic sensors and communication.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of a two-link two-or three-dimensional robot arm manipulator operating among planar or spatial obstacles, the configuration space (C-space) formed by its joint variables is a two-dimensional manifold, in which the arm maps into a point and obstacles map into simple closed curves. It has been shown that in such cases, the same approach, with some modifications, can also be applied [3]. The algorithms do not require any explicit computations of the unknown obstacles in work space or configuration space, and they guarantee convergence.…”
Section: Introductionmentioning
confidence: 99%